The influence of intravesical administration of resiniferatoxin (RTX) on the chemical coding of sympathetic chain ganglia (SChG) neurons supplying the porcine urinary bladder. - Lepiarczyk, Ewa; Majewski, Mariusz; Bossowska, Agnieszka (Histochemistry & Cell Biology, 2015)
Resiniferatoxin (RTX) is used as an experimental drug in therapy of neurogenic urinary bladder disorders. The present study investigated the chemical coding of sympathetic chain ganglia (SChG) neurons supplying porcine urinary bladder after intravesical RTX instillation. The SChG neurons were visualized with retrograde tracing method and their chemical profile was disclosed with double-labeling immunohistochemistry using antibodies against dopamine β-hydroxylase (DβH; marker of noradrenergic neurons), neuropeptide Y (NPY), vasoactive intestinal polypeptide (VIP), somatostatin (SOM), galanin, Leu-enkephalin and neuronal nitric oxide synthase (nNOS). It was found that in both the control ( n = 5) and RTX-treated pigs ( n = 5), the vast majority (90.4 ± 2.8 and 89.7 ± 2.3 %, respectively) of FB-positive (FB+) nerve cells were DβH+. RTX instillation caused a decrease in the number of FB+/DβH+ neurons immunopositive to NPY (71.1 ± 12.1 vs 43.2 ± 6.7 %), VIP (21.3 ± 10.7 vs 5.3 ± 4.3 %) or SOM (16.5 ± 4.6 vs 2.3 ± 2.6 %) and a distinct increase in the number of FB+/DβH+ neurons immunoreactive to nNOS (0.8 ± 1 vs 5.3 ± 1.9 %). The present study for the first time has provided some information that therapeutic effects of RTX on the mammalian urinary bladder can be partly mediated by SChG neurons.